Integrating Search Engine Optimization Standards into the Journalist Competency Test for Cyber Media Journalists - Dedi Sahputra; Ria Wuri Andary; Ilma Saakinah Tamsil (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
As a form of new media, cyber media requires a Journalist Competency Test (UKW) model. This study aims to determine the journalistic products produced by cyber media journalists and to design an alternative UKW model for cyber media journalists. The data was extracted from two news documentation published by mainstream media tribunews.com and detik.com, as well as test material in UKW Indonesian Journalists Association (PWI) through a qualitative content analysis approach, as well as interviews and observations from UKW implementation. The result is that there are differences in journalistic products produced by cyber media journalists compared to print media. There is a need to meet Search Engine Optimization (SEO) standards in producing journalistic products in cyber media. SEO helps online journalism compete in an increasingly competitive digital era, where audiences seek information from multiple sources. The UKW model is designed by adding SEO standards for young journalists level in test subjects 1.7. Writing News, 1.8. Editing Your Own News. For intermediate journalist level in test subjects 2.4. Writing Features, 2.6. Editing a Number of News. For main journalists level in the test subject 3.5. Determining Broadcast-worthy Coverage Material, 3.8. Writing Headlines/Comments. The UKW model with SEO content in this study can be an alternative test model to specifically test the competence of cyber media journalists. SEO models can improve journalist competence and the quality of digital journalism by providing the ability to optimize content, increase visibility, and reach a wider audience.